(3EYQGH (B"(3dG Edg EdG Gddg(B"s - (3Ydj Hf eMeO Hf YHO GdQMef Hf Ydj, CHh GdEQTGO, fhQ GdOjf GdCLghQj,J (B1066 (3g` s
(3ChdgG (B:s
(3hHYO, agPg ofHPI aj EYQGH (B"(3dG Edg EdG Gddg(B" (3SCdfj JMQjQgG HYV ef hLHJ dg GdELGHI s
(3BNQgG (B:s
(3GdNGeS bGd aj GdeZfj aj bhdg JYGdi (B"(3eG aYdhg EdG bdjd(B" (3hCfg eNGda ddeHOd efg aj Gdfaj hGdEjLGH GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B13 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B207s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B25 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdfMhs